Perioperative pain management in colorectal surgery. Issue 8 (August 2017) - Ratnalikar, Vinay; Williams, Catrin; Moses, Thomas
Abstract: Postoperative pain management has a bearing on postoperative recovery and outcomes. This is particularly so in Enhanced Recovery After Surgery (ERAS). Use of proven techniques such as central neuraxial blockade, advances in regional analgesic block techniques and the multimodal combination of drugs with newer range of adjuvant analgesics are presented. This article discusses pain management options and practices.